Тенденции восприятия индивидуально-психологических особенностей человека по частично открытому лицу - БарабанщиковВладимир Александрович; БолдыревАлександр Федорович (Психология. Журнал Высшей школы экономики, 2011)
The authors have experimentally demonstrated that the occlusion of the orthogonal parts of the face (right/left, up/down) changes the way it is perceived. These ways depend on the gender and facial structure of the model, on the position of the occlusion and the gender differences among observers. In comparison with the fully exposed face, the expression of the partly exposed face can be perceived either more or less adequately.